Prevalence, Risk Factors and Genotypes of Giardia duodenalis in Sheltered Dogs in Tuscany (Central Italy) - Andrea Agresti; Federica Berrilli; Michela Maestrini; Isabel Guadano Procesi; Enrico Loretti; Niccolò Vonci; Stefania Perrucci (Pathogens, 2021)
In sheltered dogs, the prevalence of Giardia duodenalis is frequently high and may include potential zoonotic genotypes. The prevalence, genotypes and potential risk factors of G. duodenalis were assessed in 168 dogs from four kennels (Pistoia, Prato, Florence, Valdarno) in Tuscany, central Italy and compared with data from previous Italian studies. The prevalence of other intestinal parasites was also investigated. Individual dog faecal samples collected from each kennel were examined by parasitological techniques and a rapid immunoassay for the detection of G. duodenalis and Cryptosporidium faecal antigens. On Giardia-positive samples, molecular analysis was performed for genotype identification. Overall, 69 dogs scored positive for G. duodenalis (41%), but significant differences (p ≤ 0.05) were found among the four kennels and sampling seasons. The potentially zoonotic assemblages A and B and the canine-specific assemblage C (Pistoia: A-AII, B, C; Prato: A-AII, B; Florence: A-AII; Valdarno: A and C) were identified. Toxocara canis (8.9%), Trichuris vulpis (3.6%), hookworms (1.19%) and Cryptosporidium sp. (0.6%) were also identified. The high prevalence of G. duodenalis and the identification of potentially zoonotic genotypes in all examined kennels underline the need to improve routine parasite monitoring and control measures and to provide insights into the zoonotic potential of G. duodenalis.